HOMEROOM GROUP GUIDANCE AND STUDENTS’ UNDERSTANDING OF THE RISKS OF PREMARITAL SEXUAL BEHAVIOR - Lia Rizki Innayah; Chr Argo Widiharto; Agus Setiawan (CV. TOTUS TUUS, 2026)
Premarital sexual behavior among adolescents is associated with serious health and psychosocial risks, while school-based sexual health education in Indonesia remains constrained by cultural taboos and limited structured programs. This study examined whether participation in homeroom group guidance was associated with changes in students’ understanding of the risks of premarital sexual behavior. The study employed a pre-experimental one-group pretest-posttest design involving 15 ninth-grade students at SMP Negeri 41 Semarang, Indonesia. The intervention consisted of five homeroom group guidance sessions designed to provide structured information, guided discussion, and reflective learning on the risks and consequences of premarital sexual behavior. Descriptively, students’ mean scores increased from 17.2 on the pretest to 33.9 on the posttest, with a mean difference of 16.73. The available paired-samples output indicated a statistically significant pre-post difference, t(14) = 17.83, p < .001, with an estimated large paired effect size (dz = 4.60). However, because the posttest distribution was non-normal and the study used a one-group design without a comparison group, the finding should be interpreted as preliminary rather than as conclusive causal evidence. Overall, the results suggest that homeroom group guidance shows promise as a school-based approach for improving adolescents’ understanding of sexual health risks. Future studies should employ larger samples, comparison groups, and appropriate non-parametric or robust reanalysis using raw paired data to strengthen inference.